1999
DOI: 10.1002/(sici)1521-3951(199910)215:2<987::aid-pssb987>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Static and Dynamic Properties of Liquid Less Simple Metals

Abstract: Static structure factors, S(q), thermodynamic properties and shear viscosities for liquid Zn, Cd, Hg, In, Tl, Sn, Pb, Sb, and Bi are investigated systematically. A model pseudotential which combines the sp‐ and d‐band contributions is employed to derive interionic interactions. The liquid state is described by using the thermodynamically self‐consistent variational modified hypernetted chain (VMHNC) integral equation theory, and also by using the linearised version of the Weeks‐Chandler‐Andersen (LWCA) thermod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…The RA theory for the viscosity involves the pair distribution function of hard spheres and the first and second derivatives of the partial pair potential (see below). In a study on viscosity it is reported [21] that η v (r N σ) evolves as the most dominating term for some liquid metals, while some other studies show that η v (σ) dominates [11,14,20]. Whatever be the situation, the soft part contribution is significant for a quantitative study.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The RA theory for the viscosity involves the pair distribution function of hard spheres and the first and second derivatives of the partial pair potential (see below). In a study on viscosity it is reported [21] that η v (r N σ) evolves as the most dominating term for some liquid metals, while some other studies show that η v (σ) dominates [11,14,20]. Whatever be the situation, the soft part contribution is significant for a quantitative study.…”
Section: Introductionmentioning
confidence: 88%
“…Investigation of dynamic properties specifically the viscosity and diffusion coefficient of liquid attracted the attention of physicists, chemists, metallurgists and biologists since late fifties till to date [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The reason of it is that, to understand such important material processing techniques as binary solidification and glass formation a knowledge of the liquid state diffusion coefficient is required; the rates of many industrially important reactions are controlled by the diffusion of reactant species, knowledge of viscosity is required in determining the cooling rates for glass formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the static structure factor S(q) displays a shoulder, although small, at high q-side of the main peak, similar, although less marked, to liquid Si and liquid Ge, and a coordination number (C N ) around 9-10 unlike Si and Ge that have C N around 6. Liquid Sn for its characteristic features attracted attention of theoreticians [8,[12][13][14][15][16] and experimentalists [8][9][10][11]. But to the best of our knowledge, this is the first application of the OF-AIMD method with a relatively large sample.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it should be treated as multi component system. Liquid metal structure factors resemble closely to hard sphere reference systems, and calculations to evaluate static and dynamic properties have been found to be quite reasonable in many cases [5]. It must be mentioned that short range forces primarily determine the structure of a liquid and the relatively long-range attractive part of the potential provides a uniform attractive background.…”
Section: Introductionmentioning
confidence: 99%